2008
DOI: 10.1021/ol800021r
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Ketone to gem-Diol Equilibrium by Host−Guest Interactions

Abstract: In water, N-methyl-4-(p-substituted benzoyl)pyridinium cations, BP-X, exist in equilibrium with their hydrated forms (gem-diols), whose concentrations depend on the para substituent (-X). In the presence of cucurbit[7]uril (CB[7]), the benzoyl group shows a preference for the CB[7] cavity, and the ketone to gem-diol equilibrium is shifted toward the keto form, meaning that the stabilization realized through hydrophobic interactions of the benzoyl group in the CB[7] cavity exceeds the hydrogen-bonding stabiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…[19] Recently, Rawashdeh et al have shown the control over the keto-diol equilibrium of Nmethyl-4-[(p-substituted)benzoyl]pyridinium cations through CB7 encapsulation. [28] In the present study, we report on the modulation of the ground-and excited-state proton-transfer processes of 2-…”
Section: Introductionmentioning
confidence: 89%
“…[19] Recently, Rawashdeh et al have shown the control over the keto-diol equilibrium of Nmethyl-4-[(p-substituted)benzoyl]pyridinium cations through CB7 encapsulation. [28] In the present study, we report on the modulation of the ground-and excited-state proton-transfer processes of 2-…”
Section: Introductionmentioning
confidence: 89%
“…Upfield shifts (Δ δ <0) are observed for guest protons located in the shielding region of the cavity, while guest protons located near the carbonyl oxygens of the portals experience deshielding and downfield shifts (Δ δ >0). Some caution must exercised in the interpretation of the shifts, as changes in the structures of the guest (complexation‐induced protonations,45 tautomerizations,46 etc.) and shifts in the electron density47 within the guests can overshadow simple shielding arguments.…”
Section: Complexation Of Guest Drug Moleculesmentioning
confidence: 99%
“…In addition to the shift in acid–base equilibria by the complexation of a weakly basic guest by cucurbit[ n ]uril host molecules, the modulation of other equilibria involving the cucurbit[ n ]uril inclusions of guest molecules have been reported. These include the control of base‐off/base‐on equilibria of vitamin B 12 molecules,31 cis ‐ trans isomerization of azobenzenes,45m lactone/carboxylate forms of camptothecin,44 keto‐ gem ‐diol equilibria of N‐methyl‐4‐( p ‐substituted benzoyl)pyridinium cations,46 and iminium/alkanolamine forms of sanguinarine 64…”
Section: Control Of Equilibria By Cucurbituril Complexationmentioning
confidence: 99%
“…2‐OOA was reversibly hydrated in an aqueous solution. In aqueous solution, some 2‐OOA existed in its keto form, with the majority existing as its gem diol . The keto form contained a UV chromophore, which could be excited in the near‐UV state to induce photolysis to form the radical intermediate 2‐OOA·.…”
Section: Resultsmentioning
confidence: 99%